Animal rights activism : a moral-sociological perspective on social movements - Jacobsson, Kerstin; Lindblom, Jonas (Protest and social movements., 2016)
This book develops a novel moral-sociological perspective on social movements. For the first time, Durkheim's sociology of morality is used for social movement theorizing. Nevertheless, Durkheim's approach is used as a basis for further theorization, including developing a deviance perspective on social movements. The moral-sociological framework is also useful for theorizing the role of moral reflexivity and emotion work among activists. 0This book fills a gap in existing approaches to social movements by seeing social movements as essentially moral phenomena and by conceiving of morality as a social fact, which both enables and constrains the action that activists can pursue. By doing so, it complements existing more structural, cultural or strategic action-inspired approaches to social movements. In addition, the book richly illustrates how classical sociological theory can be used in new ways to understand contemporary societies.